The unique face of comorbid anxiety and depression: increased interoceptive fearfulness and reactivity - Ironside, Maria; DeVille, Danielle C.; Kuplicki, Rayus Tiberius; Burrows, Kai Ping; Smith, Ryan; Teed, Adam R.; Paulus, Martin P.; Khalsa, Sahib S. (Frontiers in Behavioral Neuroscience, 2023)
Anxiety and depression commonly co-occur, yet the underlying brain and behavioral processes are poorly understood. Here we examined the hypothesis that individuals with comorbid anxiety and depression would show increased fearful reactivity to an aversive interoceptive perturbation relative to depressed-only individuals. 180 anxious and/or depressed participants from the Tulsa 1000 study completed multi-level behavioral or functional magnetic resonance imaging assessments of interoception and nociception including breath-hold and cold-pressor challenges, and heartbeat perception and interoceptive attention tasks. 104 individuals with comorbid depression and anxiety disorders (Dep+Anx) were propensity matched with 52 individuals with depression-only (Dep). Data were analyzed using mixed-effects linear regression. The Dep+Anx group showed significantly greater self-reported fear of suffocation during breath holding (Wilcoxon r = 0.23) and reduced cold pain tolerance (R^2 = 0.027) signified by hand removal during immersion. However, these groups did not differ with respect to neutrally-valenced behavioral indices of heartbeat perception or neural indices of interoceptive attention. Individuals with comorbid depression and anxiety, versus those with only depression, show increased respiratory fearfulness and reactivity to nociceptive perturbation, whilst showing similar interoceptive awareness during non-threatening sensations. Our findings suggest that individuals with comorbid anxiety and depression process aversive interoceptive and nociceptive signals differently than those with depression alone, providing support for a process model of increased threat sensitivity and hyperarousal in anxious depression.